Craving in Patients with Schizophrenia and Cannabis Use Disorders. (November 2013) - Schnell, Thomas; Becker, Theresa; Thiel, Maria Chantal; Gouzoulis-Mayfrank, Euphrosyne
Objective: Cannabis use is widespread among patients with schizophrenia despite its negative impact on the course of the disease. Craving is a considerable predictor for relapse in people with substance use disorders. Our investigation aimed to gain insight into the intensity and dimensions of cravings in patients with schizophrenia and cannabis use disorders (CUDs), compared with otherwise healthy people with CUDs (control subjects). Method: We examined 51 patients with schizophrenia and CUDs and 51 control subjects by means of the Cannabis-Craving Screening questionnaire. Results: We found greater overall intensity of craving and greater relief craving in patients with schizophrenia and CUDs. Reward craving was greater in the CUDs group. Relief craving was associated with symptoms of schizophrenia in patients with schizophrenia and CUDs. Conclusion: Our findings are in line with the view that aspects of self-medication or affect regulation may account (at least in part) for cannabis use in people with schizophrenia. A better understanding of the dimensions of craving may help to improve targeted therapeutic interventions that aim to reduce drug consumption in this difficult-to-treat patient group.